Challenges to the Sustainability of Exports of Indonesian Commodity Products from the European Union’s Environmental Perspective - Sidabutar, Victor Tulus Pangapoi (JURNAL BISNIS STRATEGI, 2024)
The European Union Deforestation Regulation (EUDR) aims to reduce the consumption of products entering the European Union that are linked to deforestation and forest degradation. This regulation will directly affect the global supply chain of Indonesian exports to European Union countries for palm oil products and indirectly affect importing countries as Indonesia's trading partners supply the European Union market, especially for forestry products. This could happen due to requests from Indonesian trading partners who sell their products to the European Union who apply EUDR rules. The Indonesian government needs to firmly implement supportive policies to facilitate export activities related to forest products. Apart from that, the Indonesian government must also pay attention to the impact of this regulation on Small and Medium Enterprises which will be affected because they are also importers for companies or large traders.